Growing Old and Being LGBTIQ in Malta: What Happens When We Need Care? - Christian (Magyar Gerontológia, 2025)
The present abstract explores the lived experiences of older lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ+) individuals in Malta, focusing on the intersection of ageing, care needs, and systemic disparities.